Application of Professional Standards by Forensic Service Providers in the Russian Federation - V. A. Epshtein (Теория и практика судебной экспертизы, 2018)
The legal framework for application of professional standards is analyzed, and the case is made for developing and implementing professional standards in the practice of forensic science. Priority measures are proposed towards achieving these objectives.